2022
DOI: 10.1136/jitc-2021-003735
|View full text |Cite
|
Sign up to set email alerts
|

Fc-null anti-PD-1 monoclonal antibodies deliver optimal checkpoint blockade in diverse immune environments

Abstract: BackgroundDespite extensive clinical use, the mechanisms that lead to therapeutic resistance to anti-programmed cell-death (PD)-1 monoclonal antibodies (mAbs) remain elusive. Here, we sought to determine how interactions between the Fc region of anti-PD-1 mAbs and Fcγ receptors (FcγRs) affect therapeutic activity and how these are impacted by the immune environment.MethodsMouse and human anti-PD-1 mAbs with different Fc binding profiles were generated and characterized in vitro. The ability of these mAbs to el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 47 publications
2
18
0
Order By: Relevance
“…The crystallizable fragment (Fc) of IgG antibodies can bind to Fc gamma receptors (FcγRs) and trigger effector functions like antibody-dependent cellular phagocytosis (ADCP) and antibody-dependent cell-mediated cytotoxicity (ADCC). Previous study demonstrated that Fc/FcγR interactions contribute to the resistance to PD-1 blockade, as evidenced by the depletion of activated CD8 tumor-infiltrating lymphocytes (TILs) upon application of anti-PD-1 antibody with high affinity for FcγRs ( 5 ). Importantly, blockade of FcγRs before PD-1 antibody administration prolongs PD-1 antibody binding to TILs and enhances immunotherapy-induced tumor regression in mice ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…The crystallizable fragment (Fc) of IgG antibodies can bind to Fc gamma receptors (FcγRs) and trigger effector functions like antibody-dependent cellular phagocytosis (ADCP) and antibody-dependent cell-mediated cytotoxicity (ADCC). Previous study demonstrated that Fc/FcγR interactions contribute to the resistance to PD-1 blockade, as evidenced by the depletion of activated CD8 tumor-infiltrating lymphocytes (TILs) upon application of anti-PD-1 antibody with high affinity for FcγRs ( 5 ). Importantly, blockade of FcγRs before PD-1 antibody administration prolongs PD-1 antibody binding to TILs and enhances immunotherapy-induced tumor regression in mice ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although ICI antibody developers claim that they are aware of this potential problem, and have thus modified the Fc region in their products to reduce the degree of FcγR binding, there is no evidence that these ICI antibodies lose the ability to be recognized by macrophages in vivo and antibody-bond ICI antibodies are not removed in vivo. In fact, there is study showing binding of ICI antibodies through Fc segment and depletion of antibody-bond T cells in vivo [19]. This T cell depletion mechanism may well explain the damage caused by ICI therapy in that antitumor T cells that express PD-1 are bond and removed through ADCP process.…”
Section: New Mechanism For Ici Therapy and Supporting Evidencementioning
confidence: 99%
“…Indeed, studies have demonstrated that after administration, anti-PD-1 mAb binds to tumor-infiltrating T cells at an early stage but is subsequently captured by TAMs due to the presence of Fcγ receptors, which ultimately leads to drug failure ( 53 , 54 ). More importantly, activation of Fcγ receptors by an anti-PD-1 mAb results in depletion of activated CD8 + T cells in vitro and in vivo , reducing the therapeutic effect ( 55 ). Therefore, the design of FC-null anti-PD-1 mAbs ( 55 ) or specific competitive inhibitors is one of the future strategies necessary to block Fcγ receptor-mediated resistance and increase T-cell infiltration.…”
Section: Tams Modulate the Expression And Functions Of Pd-1/pd-l1mentioning
confidence: 99%
“…More importantly, activation of Fcγ receptors by an anti-PD-1 mAb results in depletion of activated CD8 + T cells in vitro and in vivo , reducing the therapeutic effect ( 55 ). Therefore, the design of FC-null anti-PD-1 mAbs ( 55 ) or specific competitive inhibitors is one of the future strategies necessary to block Fcγ receptor-mediated resistance and increase T-cell infiltration.…”
Section: Tams Modulate the Expression And Functions Of Pd-1/pd-l1mentioning
confidence: 99%